The impact of online education on carbon emissions in the context of the COVID-19 pandemic – Taking Chinese universities as examples. (15th May 2022) - Yin, Zhaohui; Jiang, Xiaomeng; Lin, Songyue; Liu, Jin
Highlights: Due to the COVID-19 pandemic, all kinds of educational activities in countries around the world have been converted to online education. The carbon emissions from electricity consumption and transportation of college students have been significantly reduced due to the COVID-19 pandemic. Online education can significantly reduce energy consumption and lower carbon emissions. The education system has become one of the key sectors to reduce carbon emissions and promote carbon neutrality. Abstract: While the COVID-19 pandemic has had various impacts on economic and social development, it may have partially reduced human energy use, thereby helping achieve the goals of reducing carbon emissions and promoting carbon neutrality. During the pandemic, online education was widely used to replace traditional education all over the world. There is a lack of empirical studies on whether and to what extent the change of education model can reduce carbon emissions. Taking Chinese universities as cases, this study, concentrating on two main elements – transportation and electricity consumption – constructs a model and calculates the impact of online education on carbon emissions. The results show that online education can significantly reduce energy consumption and lower carbon emissions. In the field of higher education alone, the carbon emissions reduction caused by online education in half a year is equivalent to the total carbon emissions reduction of college students caused by online education during the half-year is equivalent to the total carbon emissions in 1.296 h in China, 2.688 h in the United States, 5.544 h in India, 12 h in Japan and 3.864 h in European countries of OECD. Therefore, this study suggests that the impact of online education on carbon emissions should be further studied, online education should be promoted through legislation and other systemic measures, and the goals of carbon emissions and carbon neutrality should be explored further within the field of education.